Synthesis, Molecular Characterization, Biological and Computational Studies of New Molecule Contain 1,2,4-Triazole, and Coumarin Bearing 6,8-Dimethyl - Koparir, Pelin; Sarac, Kamuran; Omar, Rebaz Anwar (Amg Transcend Assoc, 2022)
Synthesis 4-(((4-ethyl-5-(thiophen-2-yl)-4H-1,2,4-triazol-3-yl)thio)methyl)-6,8-dimethyl-coumarin and spectral analysis is carried out using the FT-IR and NMR with the help of quantum chemical calculation by DFT/6-311(d,p). The molecular electrostatic potentials and frontier molecular orbitals of the title compound were carried out at the B3LYP/6-311G(d,p) level of theory. Antimicrobial, antioxidant activity, and In vitro cytotoxic for cell lines were observed. The result shows that the theoretical vibrational frequencies, 1H-NMR and 13C-NMR chemical shift, agree with experimental data. In vitro studies showed that antimicrobial activity was weak, particularly against bacteria such as E. coli, S. aureus, P. aeruginosa, and B. cereus. The test compound's oxidative stress index (OSI) has appeared as 0.079 +/- 0.214 in antioxidant and oxidant capacity studies. The compound did not cause a harmful cytotoxic effect on healthy cell lines and showed no potential for anticancer activity on cancerous cell lines such as MCF-7 and MKN-45.
Keywords: coumarin; triazole; Gaussian; molecular modeling; cytotoxic; antioxidant